NIMG-35. TREATMENT RESPONSE ASSESSMENT MAPS (TRAMs) SENSITIVITY TO TUMOR/TREATMENT-EFFECTS AS A FUNCTION OF DATA ACQUISITION PARAMETERS. (5th November 2018) - Guez, David; Zach, Leor; Daniels, Dianne; Sharabi, Shirley; Nissim, Ouzi; Spiegelmann, Roberto; Tylim, Arielle; Taliansky, Alisa; Shoshan, Yigal; Blumenthal, Deborah; Bokstein, Felix; Cohen, Zvi; et al.
Abstract: INTRODUCTION: TRAMs calculated from delayed-contrast MRI enable reliable (sensitivity/specificity>70%) differentiation between tumor (blue in the TRAMs) and non-tumoral tissues (red). The TRAMs are calculated by subtracting 3D T1-MRIs acquired 5min (early time point) post-contrast injection from those acquired 60-105min (late point) later. Here we studied the sensitivity to tumor/treatment-effects as a function of the early T1-MRI acquisition time. METHODS: 7 patients with high grade glioma and 6 with brain metastases were scanned by the standard TRAMs protocol with the addition of a rapid 3D T1-MRI sequence (20 sec) acquired 2, 5, 12, 17, 20, 24 and 70 min post-contrast. Rapid-TRAMs were calculated using the rapid T1-MRIs, where the late time point was fixed at 70 min and the early time point changed from 2 to 24 min post-contrast. Enhancing volumes were determined on the T1-MRIs and copied to the TRAMs. Blue/tumor and red/treatment-effects volumes were calculated within the enhancing regions. RESULTS: The blue/tumor volumes, calculated from the rapid-TRAMs, increased by a factor of 4.4 ± 2.6 when moving the early time point from 2min to 15.7 ± 2.2min, where they plateaued. The increase between 5min (standard) and 15.7min was by 1.5 ± 0.3. In contrast, when moving from 2 min to 15.7min the red/treatment-effects volumes decreased by 0.7 ± 0.2, and by 0.8 ± 0.1 when moving from 5min. CONCLUSIONS: The TRAMs were shown to provide reliable differentiation between tumor/treatment-effects. The early time point is fixed at 5min post-contrast. Using shorter delays may significantly decrease the sensitivity to tumor. Still, increasing the delay to 15min may increase the sensitivity to tumor. This over-estimation of the tumor volume may be explained by the tumor vasculature clearing contrast diffusing into further brain regions surrounding the tumor. An additional 3D-T1 acquired at 15min may be applied for calculating additional TRAMs with higher sensitivity to tumor, for depicting small tumor regions.